Corneal, Conjunctival effects and blood flow changes related to silicone hydrogel lens wear and their correlations with end of day comfort. Issue 2 (April 2018) - Sorbara, Luigina; Maram, Jyotsna; Simpson, Trefford; Hutchings, Natalie
Abstract: Purpose: First, to examine how wearing high and low modulus lenses with two different base curves affected lens fit, and the corneal tissue and bulbar conjunctival vascular tissue (bulbar redness and blood velocity). Secondly, to quantify the associations between these baseline and outcome variables and the third purpose was to correlate these variables with end of day comfort. Methods: Thirty participants wore higher (PureVision (PV) 8.3, 8.6) and lower (Acuvue Advance (AA) 8.3, 8.7) modulus silicone hydrogel lenses for two weeks on a daily wear basis. Lens fitting characteristics were examined. Corneal epithelial thickness was measured and the cornea and conjunctiva were assessed. RBC velocity was estimated from high magnification bulbar conjunctival images. Subjective comfort/dryness was reported by participants using visual analogue scales. Results: AA lenses were rated the most comfortable (ANOVA, p = 0.041). The least movement was while using the AA 8.3 base curve lens (Tukey p = 0.028). Steep AA and PV lenses showed significantly higher conjunctival staining at the 2 week visit (ANOVA, p = 0.029). There was a significant decrease in RBC velocity with both steeper AA lenses vs PV lenses (Tukey, p = 0.001). Comparing baseline and 2 week visits, there was a significant negative correlation for the PV 8.3 between comfort and superior bulbar staining (r = −0.53). For both the PV 8.3 and AA 8.3 reduced RBC velocity was correlated with dryness (r = 0.61 and r = 0.91, respectively). Conclusions: Physical differences in contact lenses affect structural and vascular functional aspects of the ocular surface and these may be associated with symptoms of dryness.